Efektivitas Program Penanggulangan Kemiskinan Terhadap Penurunan Kemiskinan Di Kota Palembang Tahun 2020 - Intan Wahyuni (SOSIO DIALEKTIKA, 2022)
The poverty alleviation agenda is one of the important goals to be achieved in development. Equitable welfare and the absence of poor people are one of the world's development goals as stated in Goal 1 of the 2030 Sustainable Development Goals (SDGs), namely No Poverty. The poverty rate in the Palembang City tends to decrease from year to year, even though the decline is not significant. According to Statistics Indonesia, it was recorded that from 2019 to 2020 poverty in Palembang City only decreased by 0,01%, namely from 10,9% in 2019 to 10.89% in 2020. Palembang city government has increased poverty reduction funds by 751.18% in 2019, according to Bappeda Litbang. The reduction in poverty was not significant enough when compared to the amount of poverty alleviation program funds. This study aim to analyze the effectiveness of poverty alleviation program on the reduction of poor people in Palembang City. There are ten programs that observed in this study, namely PKH, PIP, BPNT, JKN-PBI, local goverment programs for food, children, elderly, disabilities, and other routine or non-routine programs.The effectiveness of poverty reduction programs is viewed from three aspects, namely efficiency (measured from the simulation of the absence of the program), progressivity (in terms of the value of the Coady Gross Hodinott Indicator), and the accuracy of the distribution of aid (in terms of the relative incidence, non-coverage, and leakage of program aid distribution). Based on these three aspects, it is known that the JKN-PBI program is the most effective program in Palembang City. Of all the programs implemented, only the local government's routine assistance program has 100 percent coverage of the poor. Meanwhile, other poverty alleviation programs have not covered all the poor and there are indications of leakage in the distribution of aid to the non-poor.